IMPLEMENTATION OF TODDLER GROWTH AND DEVELOPMENT DATA COLLECTION SERVICE SYSTEM AT POSYANDU IN SARWADADI VILLAGE CIREBON - sa'diyah, halimatus; Widhiani, Pahla; Jaya, Suhana Minah (Program Studi Teknik Informatika Universitas Muhammadiyah Cirebon, 2024)
P Integrated Services Post (Posyandu) is a health program used in Indonesia to improve maternal and child health at the community level with the aim of providing basic health services at the village or kelurahan level. Posyandu in Sarwadadi Village is an integrated service that has a mission to provide comprehensive services to all Sarwadadi Village residents in Cirebon. Ongoing services at the posyandu where the case study was conducted are still done manually, and the storage of toddler data and treatment data is still done in the form of books. This manual system limits the efficiency and effectiveness of health services. Therefore, efforts are needed to improve the manual system into a technological and computer-based service system. The expected result of this research is to develop a service system that can help improve the efficiency and effectiveness of services at Posyandu Sarwadadi Village, Cirebon. Key words: Posyandu, Integrated Services Post, Toddler